KESIAPAN INDUSTRI MARITIM DALAM MENYONGSONG REVOLUSI INDUSTRI 5.0 - supriyanto supriyanto (UNIMAR AMNI Semarang, 2020)
One of the most important things in life is technology. The development of technology is undeniably advanced. Indonesia have to race with these advancements. Nowadays, countries all over the world are adjusting to 4.0 industrial development era. However, some industrial experts said that several developed countries have shifted from 4.0 industrial development to 5.0 industrial revolution. The 5.0 industrial revolution leads to a thechnology-based society. In addition, technology is the key to fulfill the community’s new capabilities. According to experts, human intellegence and cognitive computing will be a combination that is needed in the 5.0 era.In the maritime industry, the 5.0 industrial revolution requires excelled maritime human resources that not only experts on economy, technology, industry but also smart. In parallel of those, Indonesia also needed to prioritize Indonesian-flag fleet, shipping manual system, infrastructures, logistics, maritime security management design, the capacity to build competencies, a qualified maritime community, the incorporated laws and regulations on shipping and maritime industry. Thiswriting was based upon study literarure. The relation of 4.0 industrial development to 5.0 industrial revolution is that all sectors must transform, especially maritime sector to make Indonesia as a world maritime axisKeywords : Maritime, technology, 4.0 Industrial development, 5.0 Industrial revolutionSalah satu hal yang sangat penting dalam menghadapi kehidupan ke depan adalah teknologi. Perkembangan teknologi tidak bisa dipungkiri semakin maju dan Indonesia harus mengikuti kemajuan tersebut. Saat ini, semua negara di belahan dunia sedang dalam taraf menyesuaikan diri dengan perkembangan industri Era 4.0, namun para pengamat industri menyatakan beberapa negara maju, telah memasuki pergeseran dari industri 4.0 menuju industri 5.0. revolusi industri 5.0 bisa mengarah pada masyarakat berbasis teknologi. Selain itu, teknologi merupakan kunci untuk mewujudkan kemampuan baru bagi masyarakat. Human intelligence dan cognitive computing, menurut para ahli akan menjadi kombinasi yang amat sangat dibutuhkan pada era 5.0.Dalam Industri Maritim, revolusi Industri 5.0 memerlukan SDM Maritim yang unggul seperti pakar ekonomi, teknologi dan industri, maupun intelijen. In paralel, diperlukan agenda prioritas seperti armada berbendera Indonesia, sistem pelayaran tetap, infrastruktur, logistik, arsitektur manajemen keamanan maritim, kompetensi capacity building, kualitas komunitas maritim, harmonisasi peraturan perundangan maupun industri strategis perkapalan dan kemaritiman. Penulisan ini didasarkan pada studi literatur. Terkait Revolusi Industri 4.0 dan Masyarakat 5.0 semua sektor harus bertransformasi, termasuk sektor maritim terlebih jika ingin menjadikan Indonesia menjadi poros maritim dunia.Kata kunci : Industri Maritim, Revolusi Industri, Industri 5.0, Masyarakat Maritim